THE EFFECT OF CASH TURNOVER, RECEIVABLES TURNOVER, AND INVENTORY TURNOVER ON PROFITABILITY IN COSMETIC SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX)2018-2023 PERIOD - Aria Saputra; Uhud Darmawan Natsir, Nurman, Anwar Ramli, Anwar (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the Effect of Cash Turnover, Receivables Turnover, and Inventory Turnover on Profitability in Cosmetic Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2023 Period. By using an associative strategy and quantitative approach, this study aims to determine the effect of independent variables on the dependent variable. The population in this study were Cosmetic Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2023 period. The sample used was 6 Cosmetic Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2023 period. The data collection technique used was documentation. The analysis method used was multiple linear regression, t- test, and F-test to obtain results regarding the effect of independent variables on the dependent variable. The results of the study showed that partially Cash Turnover had a significant negative effect on Profitability (ROA), Receivables Turnover had a positive insignificant effect on Profitability (ROA), and Inventory Turnover had a significant positive effect on Profitability (ROA). Meanwhile, simultaneously, Cash Turnover, Receivables Turnover, and Inventory Turnover jointly affect Profitability (ROA).